2005
DOI: 10.1152/ajpregu.00468.2005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of estradiol on micturition thresholds in the rat: involvement of the hypogastric nerve

Abstract: Studies have shown that the severity of bladder hyperreflexia induced by acute bladder inflammation varies with the ovarian cycle. These results suggest that the hyperreflexia is modulated by ovarian hormones. Other studies have suggested that such modulation involves the bladder's sympathetic innervation. These hypotheses were tested by assessing the development of bladder hyperreflexia in urethane-anesthetized rats subjected to different hormonal manipulations with or without bilateral hypogastric neurectomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…One could speculate that varying hormonal levels during the estrus cycle could influence the re-emergence of phasic EUS activity after SCI in females, as has been reported for female rats in a bladder inflammation model, with rats in proestrus and estrus exhibiting more severe bladder hyperreflexia than rats in metestrus and diestrus (Johnson and Berkley 2002;Dmitrieva and Berkley 2005). In addition, both estrogen and progesterone have been shown to be neuroprotective after spinal cord trauma.…”
Section: Discussionmentioning
confidence: 81%
“…One could speculate that varying hormonal levels during the estrus cycle could influence the re-emergence of phasic EUS activity after SCI in females, as has been reported for female rats in a bladder inflammation model, with rats in proestrus and estrus exhibiting more severe bladder hyperreflexia than rats in metestrus and diestrus (Johnson and Berkley 2002;Dmitrieva and Berkley 2005). In addition, both estrogen and progesterone have been shown to be neuroprotective after spinal cord trauma.…”
Section: Discussionmentioning
confidence: 81%
“…Before discussing these two effects, it is important to point out that recent studies have shown that the effects of inflammation on the bladder are influenced by the rat's reproductive status (31,32). Thus, even though estrous stage was controlled in the present study (i.e., all rats were studied in proestrus when E 2 levels are high; Freeman [33]), it is possible that the effects observed here differ in other reproductive conditions.…”
Section: Discussionmentioning
confidence: 87%
“…Numerous studies have implicated estrogens in pain modulation e.g., (Robbins et al, 1990, 1992; Sanoja and Cervero, 2005; Gintzler and Liu, 2012), including direct attenuation of TRPV1 responses to capsaicin (Xu et al, 2008). In particular, hormonal status influences bladder activity, as well as the development and severity of a number of pelvic visceral pain conditions including interstitial cystitis (Shea et al, 2000; Johnson and Berkley, 2002; Robinson and Cardozo, 2003; Dmitrieva and Berkley, 2005; Warren et al, 2011). Understanding the precise targets of estrogens in bladder sensory pathways is critical to understanding their function and potentially targeting this mechanism to modulate pain.…”
Section: Introductionmentioning
confidence: 99%